Herança digital: a (in)transmissibilidade dos bens digitais sob a ótica dos direitos fundamentais à privacidade e intimidade - Ataides, Isadora Moraes de (2024)
The present study addresses the complex issue of digital inheritance, focusing on the (in)transmissibility of digital assets from the perspective of fundamental rights to privacy and intimidation. In a contemporary context, marked by the increasing storage of personal information and digital content, there is a need for in-depth legal reflection on how these assets can be transmitted legitimately and efficiently after the death of the holder. The core of the research is the reconciliation between traditional inheritance law and the particularities of digital assets, considering the challenges faced by heirs in obtaining access, management and transmission of these assets. Analyzing practical cases and legislative developments, the study explores existing gaps and proposes alternatives for a more comprehensive and updated legal approach. The research also highlighted the relevance of the fundamental rights to privacy and intimidation in this context, balancing the interests of heirs with the preservation of the deceased's digital legacy. Through an interdisciplinary approach, this research seeks to contribute to the development of regulations that guarantee legal certainty and the protection of fundamental rights, promoting an adaptation of the legal system to the demands of the digital era. In this sense, using the bibliographical review methodology and the deductive method, we seek to analyze the first studies regarding fundamental rights in Brazil, going through the principles of privacy and intimidated both in the constitutional scope and in the scope of Civil Law and Digital Law, the which will provide a principled basis for dealing with the hereditary transmission of digital assets. In this way, it will be possible to reach a current position on the (im)possibility of transmitting specific digital goods and possible developments driven by doctrinal currents on the topic.